Toxicity of nanoparticles in plants : an evaluation of cyto/morpho-physiological, biochemical, and molecular responses - Rajput, Vishnu D.; Minkina, Tatiana M.; Sushkova, Svetlana N.; Mandzhieva, Saglara S.; Rensing, Christopher (Nanomaterial-plant interactions ;, 2022)
"Toxicity of Nanoparticles in Plants, a volume in the Nanomaterial-Plant Interactions series, reviews the latest research on toxicological effects of using nanotechnology in plants. Focusing on key themes including analyzing plant exposure to nanomaterials, mechanisms of toxicity of nanoparticles to plants, and effects, uptake, and translocation of various different nanoparticles, the book provides important insights into identifying and responding to nanoparticle presence. To date, nanotechnology is considered one of the most promising areas of research due to the widespread applications of nanomaterials in plant science and agriculture. However, extensive use of nano-based products raises concerns regarding their toxicity in crop plants, their environmental impact, and potential consequences to the human food chain. This will be an essential read for any scientist or researcher looking to assess and understand the potential toxicological risks associated with plant nanotechnology"--Page 4 of cover.